The role of immune cells and associated immunological factors in the immune response to spinal cord injury - Tang, Huaguo; Gu, Yuanjie; Jiang, Lei; Zheng, Gang; Pan, Zhuoer; Jiang, Xiugui (Frontiers in Immunology, 2023)
Spinal cord injury (SCI) is a devastating neurological condition prevalent worldwide. The pathological mechanism underlying SCI can be mainly divided into primary injury caused by initial mechanical damage and secondary injury characterized by a series of biological responses, such as vascular dysfunction, oxidative stress, neurotransmitter toxicity, lipid peroxidation, and immune-inflammatory response. Secondary injury causes further tissue loss and dysfunction, and immune response appears to be the key molecular mechanism affecting injured tissue regeneration and functional recovery from SCI. Immune response after SCI involves the activation of different immune cells and production of immunity-associated chemicals. With the development of new biological technologies like transcriptomics, the heterogeneity of immune cells and chemicals can be classified with greater precision. In this review, we focus on the current understanding of the heterogeneity of these immune components and the roles they play in SCI, including reactive astrogliosis and glial scar formation, neutrophil migration, macrophage transformation, resident microglia activation and proliferation, and the humoral immunity mediated by T/B cells. We also summarized findings from clinical trials of immunomodulatory therapies for SCI and briefly reviewed promising therapeutic drugs that are undergoing basic research.